China’s regulatory respond to plastic pollution: Trends and trajectories - Fürst, Kathinka; Feng, Yidi (Frontiers in Marine Science, 2022)
China has an international reputation as one of the largest contributors to plastic pollution in the world’s ocean. Research analyzing China’s regulatory approach to governing plastic has been limited and fragmented, and as such little is known about trends and trajectories dominating China’s plastic policy landscape. In this paper, we seek to address this gap in the literature through the construction and analysis of a complete Inventory of China plastic policy related policies from the 1st of January 2000 to the 30th of June2021. Utilizing NVIVO, our analysis of 231 Chinese plastic policy documents shows that China’s serious and concentrated effort to governing plastics really took off in the year 2016. From 2016 China saw a rapid increase in the attention paid to plastic pollution in the regulatory realm. From 2000 to the first half of 2021, the total number of Chinese plastic pertinent policies increased by a staggering 56.75 times. In this period China has also significantly transformed its approach to governing plastics, not only has the goal and purpose of regulating plastic increased in complexity, the type of plastics targeted, and the different aspects of the plastic value chain included in various policies have become increasingly comprehensive over time. Concurrently, the deployment of different types of regulatory instrument utilized for the purpose of governing plastics in China has become much more diversified, with a major focus on prohibitive bans and information campaign currently dominating Chinese plastic policy instrument. Economic policy instruments, especially economic incentives have only recently been gaining popularity. Finally, today most government agencies have published policies which are relevant for the regulation of plastic pollution control and prevention in China. China’s fairly recent plastic policy awakening, should be understood in light of China’s focus on circular economy, the county’s ramping up of regulatory focus and fiscal investment in solid waste management and pertinent infrastructure. Lastly, we point to some possible trajectories on China plastic policy landscape, highlighting the synergies between reducing plastic production, consumption and waste treatment and China’s carbon neutrality ambition, and well as predicting a stronger policy focus and emphasis on plastic cleanup efforts.